Taxonomy and conservation of Philippine Cycads - Madulid, Domingo A. (Animo Repository, 2009)
Six species of cycads are recorded in the Philippines, three of which are endemic. The different species of cycads can be recognized by the characters of the microsporophylls, megasporophylls, and seeds. The current conservation status of the different species of Cycas is assessed and categorized using the IUCN criteria on basis of currently available information. © 2009 Nationaal Herbarium Nederland.